Punishment and rehabilitation – Uneasy bedfellows under section 44 of the Crime and Courts Act 2013 - Freer, Elaine AO (The Australian and New Zealand journal of criminology, 2017)
Over the last 25 years, community sentences have evolved significantly. However, throughout this period there has been a consistent theme of rehabilitation underpinning them. Section 44 of the Crime and Courts Act 2013 has set out, the author argues, to alter this by requiring that a punitive element is attached to a Community Order given under s177 Criminal Justice Act 2003 unless to do so would be ‘unjust in all the circumstances’. Considering the types of offenders for whom community penalties have been shown to be particularly useful in reducing recidivism, and the potentially high threshold of ‘unjust in all the circumstances’, it is argued that this requirement will compromise the strengths previously exhibited by Community Orders and considers why such a requirement may have been added.